Enhancing Numeric Literacy through Creative Mathematical Reasoning in the Merdeka Belajar Curriculum Framework - Inelsi Palengka; Lusiana Delastri; Tiara Indah Belopadang (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study investigates the effectiveness of creative mathematical reasoning in improving students' numeracy literacy within the framework of the Independent Learning Curriculum. Numeracy literacy is a crucial competency that enables learners to comprehend and address real-world problems using mathematical concepts and skills. The Merdeka Learning Curriculum provides space for innovative approaches in learning, including the application of creative mathematical reasoning to improve students' numeracy literacy skills. Using a quantitative quasi-experimental design, the study involved junior high school students divided into two groups: an experimental group and a control group. The findings revealed that the experimental group achieved a higher average score (M = 78.9; SD = 10.53) compared to the control group (M = 67.8; SD = 5.30). Statistical analysis using paired and independent t-tests confirmed a significant improvement in the performance of the experimental group (p < 0.05). The results demonstrate that creative mathematical reasoning significantly enhances students' comprehension, critical thinking, and problem-solving skills. The study concludes that integrating creativity-based reasoning strategies is aligned with the Independent Learning Curriculum and offers valuable guidance for teachers to design more innovative, student-centered math learning experiences.